2009
DOI: 10.1186/1471-2334-9-78
|View full text |Cite
|
Sign up to set email alerts
|

Impact of infection control activities on the rate of needle stick injuries at a tertiary care hospital of Pakistan over a period of six years: an observational study

Abstract: BackgroundAccidental exposure to blood and body fluids is frequent among health care workers. They are at high risk of nosocomial transmission of blood borne pathogens due to injuries caused by used sharps. We are reporting impact of surveillance and educational program on the rate of needle stick injuries among health care workers at a tertiary care hospital in Pakistan.MethodsAt Aga Khan University Hospital sharp injuries are reported to infection control office. To reduce these incidents a quality improveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
48
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 24 publications
(24 reference statements)
7
48
2
1
Order By: Relevance
“…• The frequency of the sharps injuries can substantially be reduced by target education to the technicians and the nurses [15,[17][18][19][20]]. …”
Section: Resultsmentioning
confidence: 99%
“…• The frequency of the sharps injuries can substantially be reduced by target education to the technicians and the nurses [15,[17][18][19][20]]. …”
Section: Resultsmentioning
confidence: 99%
“…Even though there were methodology and study site differences, our study was in line with Pakistan, Ugandan and Ethiopian studies. A study in Pakistan, and Uganda showed that lack of training was the main factors leading to needle stick injuries, 10,12 working for more than 40hour per week, recapping needles and not using gloves when handling needles were associated factors. 12 A recent study in FHRH also identified suboptimal practices and behaviours that put them at risk to the injury.…”
Section: Discussionmentioning
confidence: 99%
“…The most common reasons are two handed recapping, and the unsafe collection and disposal of sharps waste. 10 Two millions NSI are reported in health care providers every year.…”
mentioning
confidence: 99%
“…Multiple studies have reported a decline in PI rates after implementing multifaceted approaches, including education [16][17][18][19][20][21]. Other studies have stated that education plays a major role in augmenting knowledge and promoting safe behavior among HCWs [17,[24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found that education is an essential component of every intervention and can be effective on its own [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 97%